Comparative effects of high-intensity interval training versus moderate-intensity continuous training on body composition and blood pressure in overweight adolescents: a systematic review and meta-analysis of randomized controlled trials - Li, Xilin; Cui, Zhibo; Tan, Zhijun; Li, Jiangxuan; Yang, Chengbo (Frontiers in Physiology, 2025)
Background and aimsAdolescent overweight and obesity are increasing worldwide, posing a growing public health concern. Although both HIIT and MICT have been shown to reduce body fat and improve cardiovascular fitness, few studies have directly compared their effects in adolescents. This study therefore systematically evaluates their impact on body composition and blood pressure to inform appropriate exercise recommendations.MethodsAn extensive database search was undertaken involving six sources—such as PubMed, Web of Science, and the Cochrane Library—employing predetermined search terms to locate randomized controlled trials. The search covered literature published up to February 20, 2025, starting from each database’s inception. The methodological rigor of the selected studies was evaluated through a revised evaluation approach based on PRISMA guidelines. Finally, the influence of the two exercise modalities on adiposity reduction and blood pressure in overweight/obese adolescents was analyzed and discussed.ResultsAn overall number of 16 randomized controlled trials (RCTs), comprising 473 eligible participants, were incorporated into the analysis. The findings revealed that: (1) HIIT was superior in decreasing body fat percentage [MD = −0.74, 95% CI (−1.44, 0.04), Z = 2.74, P = 0,04]. There was no statistically relevant difference detected between the two groups in body weight, body mass index, fat-free mass, or blood pressure. (2) Subgroup analysis indicated that MICT was more effective in reducing waist circumference when running was used as the mode of exercise intervention [MD = 2.81, 95% CI (0.36, 5.26), Z = 2.25, P = 0.02].ConclusionBoth HIIT and MICT demonstrated comparable effects on most outcomes in overweight/obese adolescents. HIIT showed a modest, borderline significant advantage in reducing body fat percentage, while MICT appeared more effective in reducing waist circumference in the running subgroup. Further high-quality studies are needed to confirm these findings and guide exercise recommendations.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42025639229.